STATUS AND DEVELOPMENT TRENDS OF MIGRATION PROCESSES IN RUSSIA. THE INFLUENCE OF MIGRATION PROCESSES ON THE STATE OF THE LABOUR MARKET - E. D. Katulskij (Модернизация, инновация, развитие, 2016)
The article examines trends in labour migration in the Russian Federation. Analyzed the migration of communications of Russia in the 1st quarter 2014 and 2015, Examines the impact of increasing migration fl ows of citizens of Ukraine on the state of the labour market of Russia. Supporters of immigration openness believe that increased migration is one of the ways of solving demographic problems of Russia and problems of replenishment of the labour market. Their opponents believe that immigration creates excess supply in the labor market by allowing employers to permanently reduce the level of remuneration and social guarantees, worsen working conditions.